Genomic analysis of Skermanella stibiiresistens type strain SB22T. Issue 3 (November 2014) - Zhu, Wentao; Huang, Jing; Li, Mingshun; Li, Xiangyang; Wang, Gejiao
Abstract Members of genusSkermanella were described as Gram-negative, motile, aerobic, rod-shaped, obligate-heterotrophic bacteria and unable to fix nitrogen. In this study, the genome sequence ofSkermanella stibiiresistens SB22T is reported. Phylogenetic analysis using core proteins confirmed the phylogenetic assignment based on 16S rRNA gene sequences. Strain SB22T has all the proteins for complete glycolysis, tricarboxylic acid cycle and pentose phosphate pathway. The RuBisCO encoding genescbbL1S1 and nitrogenase delta subunit geneanfG are absent, consistent with its inability to fix carbon and nitrogen, respectively. In addition, the genome possesses a series of flagellar assembly and chemotaxis genes to ensure its motility.